2021
DOI: 10.1371/journal.pone.0252208
|View full text |Cite
|
Sign up to set email alerts
|

Social capital and cognitive decline: Does sleep duration mediate the association?

Abstract: Background Studies have found that social capital (SC) is associated with the risk of cognitive decline; however, the mechanism explaining how SC leads to cognitive decline is unclear. The current study examines the mediation effect of sleep duration on the relationship between SC and cognitive decline in Chinese older adults. Methods A cross-sectional study of 955 community-dwelling aged 60 or over was conducted. The mini-mental state examination (MMSE), self-report sleep duration questionnaire, and social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Five studies used the diagnostic criteria of Albert et al [ 59 , 66 , 85 , 92 , 108 , 120 ]. Four studies used the “Mini-Mental State Examination—MMSE” [ 121 ] as a diagnostic criterion, with different cut-offs: MMSE lower than 24 [ 91 ], MMSE lower than 20 [ 78 ], MMSE lower than 21 [ 80 ], MMSE lower than 17 [ 109 ]. Seven studies adopted other criteria [ 122 , 123 , 124 , 125 ], for example, Portet et al criteria [ 63 , 65 , 75 , 88 , 95 , 98 , 107 , 109 , 122 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies used the diagnostic criteria of Albert et al [ 59 , 66 , 85 , 92 , 108 , 120 ]. Four studies used the “Mini-Mental State Examination—MMSE” [ 121 ] as a diagnostic criterion, with different cut-offs: MMSE lower than 24 [ 91 ], MMSE lower than 20 [ 78 ], MMSE lower than 21 [ 80 ], MMSE lower than 17 [ 109 ]. Seven studies adopted other criteria [ 122 , 123 , 124 , 125 ], for example, Portet et al criteria [ 63 , 65 , 75 , 88 , 95 , 98 , 107 , 109 , 122 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nine [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ] studies reported data from AD people and twenty-four [ 63 , 65 , 66 , 68 , 69 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 100 , 101 , 102 , 103 , 106 , 107 , 109 ] studies on people with MCI diagnosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 Each item was measured using a 1–5 Likert scale in which 1 represents strongly disagree and 5 represents strongly agree: 1) People around here are willing to help their neighbors, 2) People in my neighborhood generally get along with each other, 3) People in my neighborhood can be trusted, and 4) People in my neighborhood share the same values. The Cronbach’s alpha was 0.81 among the Chinese general population, 22 and 0.96 for patients with T2DM.…”
Section: Methodsmentioning
confidence: 96%
“…The higher the score indicates the greater the social capital of the participant. Both instruments are widely used to assess the social capital of Chinese adults [ 35 , 36 ], the Cronbach’s alpha in this sample is 0.86.…”
Section: Methodsmentioning
confidence: 99%